Is there unique difference in the type of renal stones in Northern Sri Lanka? Analysis of chemical composition of renal stones in Jaffna by infrared spectroscopy - Rajendra, S. (Research gate, 2020)
Renal stone disease is a common clinical problem in surgical practice. Renal stone is a common cause for obstructive uropathy and renal impairment. Because of differing “aetio- pathology”, kidney stones are usually mixtures of two or three or more chemical components. Analysis of chemical composition and type of renal stone could aid in the prevention and management of stone formation and its recurrence. The comparison of the prevalence of renal stone types in Northern Sri Lanka with other geographical regions can help in the identification of possible environmental “geo- chemical” factors associated with nephrolithiasis.
Keywords: Renal stone; Chemical composition; Staghorn & Non staghorn calculi